[(0.24*5)+ (0.66*5)] == 4.50
0.24x5 = 1.20
0.66x5 = 3.30
+ ____
4.50
27.00÷4.5 = 0.166666667
Answer:
x³ - 8x² - 11x + 148
Step-by-step explanation:
Given that x = 6 + i is a root then x = 6 - i is also a root
Complex roots occur as conjugate pairs.
The factors are therefore (x - (6 + i)) and(x - (6 - i))
Given x = - 4 is a root then (x + 4) is a factor
The polynomial is the product of the factors, that is
p(x) = (x + 4)(x - (6 + i))(x - (6 - i))
= (x + 4)(x - 6 - i)(x - 6 + i)
= (x + 4)((x - 6)² - i²)
= (x + 4)(x² - 12x + 36 + 1)
= (x + 4)(x² - 12x + 37) ← distribute
= x³ + 4x² - 12x² - 48x + 37x + 148
= x³ - 8x² - 11x + 148
<span><span><span>1/2</span><span>(<span><span>2g</span>−3</span>)</span></span>=<span>−<span>4<span>(<span>g+1</span>)</span></span></span></span>
<span><span><span>1/2</span><span>(<span><span>2g</span>−3</span>)</span></span>=<span>−<span>4<span>(<span>g+1</span>)</span></span></span></span>
<span><span>g+<span><span>−3/</span>2</span></span>=<span><span>−<span>4g</span></span>−4</span></span>
<span><span><span>g+<span><span>−3/</span>2</span></span>+<span>4g</span></span>=<span><span><span>−<span>4g</span></span>−4</span>+<span>4g</span></span></span><span><span><span>5g</span>+<span><span>−3</span>2</span></span>=<span>−4</span></span>
5g+−3/2+3/2=−4+3/2
<span><span>
5g</span>=<span><span>−5/</span>2</span></span>
<span><span><span>5g/</span>5</span>=<span><span><span>−5</span>2</span>5</span></span><span>
g=<span><span>−1</span><span>2
Hoped I helped!</span></span></span>